Pengaruh Budaya Organisasi Dan Kompensasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening (Jurnal Kendali Akuntansi, 2023)
This research was related to the influence of organizational culture and compensation on employee performance PT. Armada Financial Magelang with job satisfaction as an intervening variable. The purpose of this study was to: determine the influence of organizational culture on job satisfaction partially. Knowing the influence of compensation on job satisfaction partially determine the influence of organizational culture and job satisfaction on organizational commitment simultaneously, knowing the influence of organizational culture on employee performance partially determine the effect of job satisfaction on employee performance partially determine the influence of organizational culture and job satisfaction the performance of employees simultaneously, and knowing where greater direct influence organizational culture and job satisfaction on employee performance PT Mega Finance Mojokerto with indirect and direct influence of organizational culture and job satisfaction on employee performance PT Mega Finance Mojokerto through organizational commitment. Respondents in this study were 58 employees of PT Mega Finance Mojokerto. Data collection methods used are questionnaires and in analyzing the data using path analysis. The results of this study indicated that there was partial significant effect of organizational culture on job satisfaction, there was partial significant effect of compensation on job satisfaction, there was significant effect of organizational culture and compensation on job satisfaction simultaneously, there was partial significant effect of organizational culture on employee performance, there was partial significant effect of job satisfaction on employee performance, there was partial significant effect of organizational culture and job satisfaction on employee performance simultaneously, there was partial significant effect of job satisfaction to employee performance. Then simultaneously significant effect of job satisfaction to employee performance. In addition, the indirect influence of organizational culture on employee performance through job satisfaction PT Mega Finance Mojokerto greater than the direct influence of organizational culture on employee performance. Indirectly influence compensation on employee performance through job satisfaction PT Mega Finance Mojokerto greater than the direct effect of compensation on employee performance.